MEKARE-KARE TRADITION AS SPORTSMANSHIP AND CULTURAL RESILIENCE - Putu Ronny Angga Mahendra; I Made Erpan; Rini Julita Maitang (International Conference on Multidisciplinary Research Perspective, 2025)
This study explores the Mekare-kare tradition as a means of cultivating sportsmanship and cultural resilience. Mekare-kare, a traditional ritual from Tenganan Pegringsingan, Bali, involves a mock battle with pandan leaves. The research employs a qualitative approach with a case study design, gathering data through interviews, observation, and document analysis. The findings reveal that Mekare-kare embodies values of respect, discipline, and humility, fostering fair play and cultural identity. It serves as a platform for community engagement, cultural preservation, and character education, highlighting the potential of local traditions in shaping a generation that is both competitive and culturally aware. This tradition also fosters values for individuals to maintain their culture in the face of globalization and modernization.